Lanthanide-based inorganic-organic hybrid materials for photon-upconversion - Muhammad Safdar; Amr Ghazy; Mika Lastusaari; Maarit Karppinen (ROYAL SOC CHEMISTRY, 2022)
Photon-upconversion materials are capable of converting low energy infrared light into higher energy visible or ultraviolet light. Such materials are demanded for applications such as deep-tissue imaging, cancer therapy, nano-thermometry, biosensing, display and solar-cell technologies, and beyond. Trivalent lanthanide ions are promising materials for upconversion due to their suitable f-orbital energy levels allowing absorption in the near-infrared and emission in the visible wavelength range. The major obstacle in realizing the full potential of the Ln-based upconverters is their characteristically small absorption cross-sections. As many organic molecules possess much larger absorption cross-sections, their combination with Ln3+ ions could bring about remarkable mutual benefits. Additionally, the organic ligands can also function as spacers to yield metal–organic framework type upconverting materials. Indeed, superior upconverting properties have already been reported for a diverse family of Ln-based inorganic–organic hybrids. Here we present an account of the recent developments in the field of Ln-based inorganic–organic upconverting materials and their emerging applications.